SOCIAL INFLUENCE AND ONLINE IMPULSE BUYING OF INDONESIAN INDIE COSMETIC PRODUCTS - Andhari Shanty Kusmaharani; Rizal Edy Halim (Universitas Mercu Buana, 2020)
As part of social influence, online reviews provide important information and peers as consumer socialization agents had shown that they affect on consumers’ online shopping behavior. This study aims to identify how Indonesian indie cosmetic products can generate online impulse buying. To do so, a research model combining theories of online reviews and peers influence along with browsing and peer communication was used. Further, this research had 173 participants on the online survey that was conducted in Greater Area of Jakarta, Indonesia. The data results were analyzed using structural modeling equation, specifically partial least square method. Results show how hedonic value of online reviews have influence on browsing while tie strength with peers and identification with peer group have influence on peer communication; that then encourage urge to buy impulsively that stimulates impulse buying behavior.